Implementation Of Life Cycle Cost in The Bus Station Building - Damanik, Divan Yoan Alvino (Jurnal Teknik Sipil, 2024)
With the increase in existing development, of course, there must be consideration of careful cost planning to support planning, use, and the end of the building service period, particularly in the building industry. The use of the LCC method in estimation is one part of estimating the service life. Both qualitative and quantitative methodologies were used in this investigation.. The research refers to the terminal development project, and takes a sample of the building which is the focus of the research. The Budget Plan, containing each of its elements, is also the foundation of the research. The building's service life is then estimated and considered to be 25 years of operation., the resulting life cycle cost is Rp. 20,499,410,364, - The largest cost during the service life of the building is 25 years, which is found in operational costs Rp. 9,302,325,418 (40.86%), the initial cost is Rp. .7,769,441,715 (34.12%), maintenance costs Rp. 2,312,949,413 (10.16%), replacement cost Rp.2,249,032,308 (9.88%) and salvage value Rp.1,134,338,490 (4.98%).